Benthic macroinvertebrates functional feeding group community distribution in rivers connected to reservoirs in the midstream of Citarum River, West Java, Indonesia - FIKRI ILMI; BARTI S. MUNTALIF; NURUL CHAZANAH; NAVISYA E. SARI; SATRIA W. BAGASKARA (Society for Indonesian Biodiversity, 2023)
Abstract. Ilmi F, Muntalif BS, Chazanah N, Sari NE, Bagaskara SW. 2023. Benthic macroinvertebrates functional feeding group community distribution in rivers connected to reservoirs in the Midstream of Citarum River, West Java, Indonesia. Biodiversitas 24: 1773-1784. An imbalance in the composition of the feeding groups can indicate a disturbed environment; therefore, in recent years, feeding group composition analysis has been widely used by academics to assess the health of river ecosystems. This research aims to describe the general distribution of functional feeding groups related to their habitat condition. The research was conducted in the midstream of the Citarum River, around the Saguling, Cirata, and Jatiluhur Dams of West Java Province, Indonesia. The midstream Citarum region starts from the Margaasih Sub-district, Bandung District (before Saguling Dam) to the Jatiluhur Sub-district, Purwakarta District (after Jatiluhur Dam). The research was conducted from July to September 2022. Environmental data, including water and sediment samples, were taken monthly, whereas benthic macroinvertebrates samples were taken every two weeks using a Surber net. Benthic macroinvertebrates samples were then classified based on their species and feeding group. In addition, water pollution levels were classified based on Nemerow Pollution Index. Pollution levels and sediment characteristics were then tested for correlation with the benthic macroinvertebrate feeding group distribution. In general, in midstream Citarum, gathering collectors are the group with the highest relative abundance (82.64%), followed by scrapers (35.6%), predators (11.66%), and filtering collectors (2.14%). Based on Pearson's correlation, environmental conditions such as pollution and types of substrates have several negative correlations with the distribution of functional feeding groups. A dam in the midstream Citarum region has proven to affect environmental conditions. Differences in flow velocity, substrate characteristics, physicochemical quality of water, and pollution levels characterize this.